Machismo: Competing Over Honor (studies of Sicilian experience) - Žvinklienė, Alina (Sociologija. Mintis ir veiksmas, 2005)
The article analyzes „machismo“ as a cultural phenomenon which attains international significance because the processes of globalization on the one hand and of gender studies on the other. The concept of „machismo“ and its derivate „macho“ becomes a buzz-word in the eveday discourses in the english-speaking world. The aim of the article is to define the concept of „machismo“ and to develop a sociological interpretation of the concept of „honor“.
Keywords: machismo; honor; globalization; feminism and gender studies